Transformation of Organic Residues and its Relationship to Soil Development Under High Altitude Forests - Dhir, R. P. (Indian Forester, 1970)
Samples of foliage of principal tree species, litter, raw humus layer and soil underneath were collected at typical sites under principal forest formations occurring in the altitude range of 2,300-3,600 m above m s.l. in an area of Himachal Pradesh in the North-western Himalayas. Samples of vegetation and litter were analysed for their ash content as also for the various chemical elements present in the ash in order to understand the nature and the changes that take place with increasing degree of decomposition and mineralisation under natural conditions. An attempt has been made to bring out the relationship that these organic layers have with the physico-Chemical properties of the soil and this has been compared with the relationship observed in the forest areas of more northerly latitude in Europe.